Occupational Therapy Assessment for Upper Limb Rehabilitation: A Multisensor-Based Approach - Mahmoud, Seedahmed S.; Cao, Zheng; Fu, Jianming; Gu, Xudong; Fang, Qiang (Frontiers in Digital Health, 2021)
Majority of post-stroke patients suffer varying degrees of upper limb function and fine motor skills impairment. Occupational therapy (OT) with other rehabilitation trainings is beneficial in improving the strength and dexterity of the impaired upper limb. However, upper limb OT programs should be prescribed based on an accurate upper limb assessment. In this paper, we propose a novel multi-sensor method for upper limb movements assessment using kinematic and physiological devices to capture the limb motions and the surface electromyogram (sEMG), respectively. These sensors are Kinect, inertial measurement unit (IMU), Xsens, and sEMG. Experimental results show that the overall accuracy of the OT based motion classification is 82.2 %. Moreover, the fused Kinect and Xsens data show a high correlation with muscle strength giving a correlation coefficient (CC) of 0.88. The outcome of this research envisages to assist occupational therapy specialists as well as promotes early support discharge; hence could be a possible solution in alleviating the great stress that the healthcare system is currently experiencing worldwide.